1996
DOI: 10.2527/1996.7471462x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary magnesium level on metabolic and growth-performance responses of feedlot cattle to laidlomycin propionate.

Abstract: A metabolism trial and a growth-performance trial were conducted to evaluate the interaction of dietary magnesium level (.18 vs .32%) and laidlomycin propionate (LP) (0 vs 11 ppm, airdry basis) on utilization of a high-energy finishing diet by feedlot steers. There were no treatment effects (P > .10) on ruminal and total tract digestion of OM and ADF. However, there was an interaction (P < .05) between magnesium level and LP on ruminal starch digestion. With LP, magnesium level had no effect on ruminal starch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
3
3
1
Order By: Relevance
“…This difference may have occurred due to diarrhea in the animals receiving supplementation, leading to increased gastric emptying pre-slaughter. These data are contradictory to other experiments (Zinn et al, 1996;Apple et al, 2005), who found no change in yield.…”
Section: Resultscontrasting
confidence: 99%
“…This difference may have occurred due to diarrhea in the animals receiving supplementation, leading to increased gastric emptying pre-slaughter. These data are contradictory to other experiments (Zinn et al, 1996;Apple et al, 2005), who found no change in yield.…”
Section: Resultscontrasting
confidence: 99%
“…This amounts to a reduction in dietary ME of 0. Consistent with previous studies (Bauer et al, 1995;Zinn et al, 1996;Ramirez et al, 1998), laidlomycin supplementation did not affect (P>0.20) carcass characteristics. Likewise, variation i n supplement concentration did not affect (P > 0.20) carcass characteristics (Table 2).…”
Section: Resultssupporting
confidence: 80%
“…Typically, concentrations of total VFA are not affected, but molar proportions of propionate are increased and acetate and butyrate are decreased compared with unsupplemented controls (Raun et al, 1976;Chalupa et al, 1980). Laidlomycin propionate has been reported to affect ruminal VFA concentrations in a similar fashion, except for butyrate, which is not altered (Galyean et al, 1992;Zinn et al, 1996;Campbell et al, 1997). Ionophore effects on ruminal VFA concentrations in the growth and ruminal metabolism experiments agree with these observations.…”
Section: Ruminal Characteristicssupporting
confidence: 65%
“…Galyean et al (1992) noted LP supplementation increased the ruminal NH 3 N concentration of steers offered a concentrate diet. In addition, Zinn et al (1996) reported LP increased duodenal flow of NH 3 N for steers, suggesting an increased ruminal NH 3 N concentration. Therefore, we conducted two experiments to evaluate the effect of LP on steer growth and ruminal N metabolism.…”
Section: Introductionmentioning
confidence: 94%